Nanoyeast Supported on Silica Gel for The Continuous Flow Bioethanol Production - Swara Pancholi; Parth Naghera; Manan Shah; Indra Neel Pulidindi; Suresh Selvaraj; Prakash Vaithyanathan (International Journal of Advance in Molecular Engineering, 2024)
Nanomaterials outperform their bulk counterparts. Yet, production of nanomaterials, especially, nanoyeast is a challenge and is an upcoming field. Yeast is a fungal strain that consumes carbohydrates (glucose, sucrose, molasses and the like) and produces bioethanol, a potential transportation fuel. Impregnation methods are well known in catalysis to yield nanomaterials via better dispersion. An attempt has been made to modulate the size of yeast to increase the efficiency of carbohydrate conversion into bioethanol. Effective adsorbent, namely, silica gel, is developed to disperse small particles of yeast on the support. The supported biocatalyst (nanoyeast/silica gel) thus produced was packed in a fixed bed flow reactor. From a reservoir held vertically above the packed bed reactor, the carbohydrate feedstock (10 wt.%) was passed through the reactor. The reactor was packed with 50 g of the silica gel loaded with nanoparticles of yeast. In a very first attempt of its kind, successful conversion of sucrose to bioethanol is obtained at a modest flow rate of the feed. The product collected at the outlet after 24 hours of fermentation process in the fixed bed continuous flow reactor was characterized by 1H NMR to see the potential of the nanoyeast under modest loadings for the fermentation of carbohydrates. Indeed, the formation of bioethanol was observed in the 1H NMR spectrum (a 2 H, q at 1.029 ppm, and 3 H, t at 3.65 ppm) of the aliquot collected after 24 h of the fermentation of sucrose by the nanoyeast. This evidence is good enough to prove the formation of bioethanol from the metabolism of sucrose by the nanoyeast. However, in addition to peaks typical of bioethanol, the signals characteristic of unreacted sucrose were also seen. This shows that further optimization of the process is required. Thus a new avenue is opened to modulate the size of yeast particles using mild ultrasound irradiation (40 kHz) as a dispersing field and silica gel as dispersing medium. Much remains to be done in this direction pertaining to the characterization of the nanoyeast/silica gel biocatalyst. With the kind of synthetic strategy developed, even with no yeast particles visible to the naked eye, the supported catalyst could convert sucrose to bioethanol. It is, at the moment, surmised that the activity of the catalyst is attributable to the nanoyeast. However, detailed characterization of the size of the yeast particles with scanning electron microscopy is warranted, which will be a subject of our next communication.
Keywords: Bioethanol; Fermentation; continuous flow process; glucose; nanoyeast; silica gel; support